Learning Patterns of Social Fiqh in Pesantren: A Learning Theory Perspective - syaefudin achmad; Miftahuddin; Muhammad Aji Nugroho Aji Nugroho; Muhammad Aiman Awalluddin (Pendidikan Agama Islam, Fakultas Ilmu Tarbiyah dan Keguruann, IAIN Syekh Nurjati Cirebon, 2026)
This study aims to analyze the learning patterns of social fiqh in Islamic boarding schools (pesantren) from the perspective of learning theory. Social fiqh is understood as an approach to Islamic jurisprudence that is not solely oriented toward normative-legal understanding, but also toward the internalization of social values and the formation of students’ social piety. This research employs a qualitative approach with a case study design conducted at Pesantren Ath-Thohiriyyah in Purwokerto City. Data were collected through in-depth interviews, participant observation, and document analysis, involving kiai, ustaz, students, and pesantren administrators. Data analysis was carried out using the interactive model developed by Miles and Huberman consisting of three main procedures: data condensation, data display, and conclusion drawing. The findings indicate that social fiqh learning in pesantren is implemented through three main patterns: (1) a textual–normative pattern based on the study of kitab kuning (classical Islamic texts); (2) a contextual–applicative pattern through students’ engagement in socio-religious practices; and (3) a cultural–habituative pattern through daily practices and pesantren traditions. From the perspective of learning theory, these findings reflect the integration of behaviorist, constructivist, social learning, and contextual learning approaches within a coherent pesantren educational system. This study affirms that pesantren function as contextual and transformative learning spaces capable of bridging fiqh texts and social realities, thereby contributing to the formation of students who possess both individual and social piety. Keywords: Social Fiqh; Pesantren; Learning Patterns; Learning Theory.